An overview on the time series of geodetic and GPS network of Nepal (Journal on Geoinformatics, Nepal, 2003)
This paper makes an overview of different geodetic and GPS networks of Nepal established in different time, with different accuracies and with different objective. Before 1945 the importance of surveying and its application was poorly understood in Nepal, therefore the surveys were limited to the measurement of land parcel covering a small area, considering it as a plane. After launching the land reform policy HMG/ Nepal 1963 and also because of the various development project, the importance and the requirement of establishing the geodetic control, defining the ellipsoidal shape of the earth as the reference surface is felt necessary in the country for the surveying and mapping activities. Interestingly various countries has been involved in establishing the high precision geodetic networks in the time series of evolution of scientific mapping in the country. Different networks being established by different institutions but very little interest had been given in integrating them. As a result problem persists in understanding and integrating spatial measurements in the geodetic field of survey department. This literature tries to identifythe existing problems in defining the relationships between the networks and demonstrates the status of existing geodetic and GPS network of Nepal.